Effect of Brucella Infection on Reproduction Conditions of Female Breeding Cattle and Its Public Health Significance in Western Tigray, Northern Ethiopia - Mekonnen Haileselassie; Shewit Kalayou; Moses Kyule; Mekonnen Asfaha; Kelay Belihu (Veterinary Medicine International)
The most common clinical manifestations of brucellosis in livestock are associated with reproduction. This paper reports the result of a cross-sectional study conducted between October, 2007 and April, 2008 in Western Tigray, North Ethiopia, with the objectives of assessing the effect of Brucella infection on reproduction conditions of female breeding bovine and to explore the presence of Brucella seroreactors in vulnerable humans. A total of 1,354 and 246 sera were collected from female cattle and humans, respectively. The sera were screened using Rose Bengal plate test (RBPT), and positive samples were confirmed by complement fixation test (CFT). Reproductive conditions for female cattle and risk to human brucellosis seropositivity were tested by using logistic regression analysis. The result indicated that the overall prevalence in female cattle was 6.1%. The study showed 1.2% prevalence among human risk groups, all of which were herdsmen. Logistic regression identified parity status, calving interval, abortion history, and abortion period were significantly associated with seropositivity. The association was not significant with reproductive status and parity number. Proper hygienic practices and team work between veterinary and health personnel should improve the efforts to combat disease transmission.